Expression and clinical significance of PD-1 in UCEC and its Impact on tumor: PD-1 in UCEC and its Impact - Xing, Fengjuan; Yang, Yan; Zheng, Wei (Cellular and Molecular Biology, 2023)
Programmed death 1 (PD-1) plays an important role in the immune escape, occurrence and development of tumors by inhibiting the function of immune cells. However, its prognostic value in uterine corpus endometrial carcinoma (UCEC) and its impact on the tumor microenvironment remain to be further explored. Transcriptional datasets were retrieved from the GEPIA, TIMER and TCGA databases. “edgeR” package was used for the identification of differentially expressed genes (DEGs) between two groups of patients (PD1-high and PD1-low group). Gene set enrichment analysis (GSEA) was performed to identify underlying pathways between betweenPD1-high and PD1-low groups functioning in UCEC. Gene Correlation Analysis was used to further confirm the associations of PD1 expression with T-cell-related genes. Cytoscape software was used to identify hub genes in DEGs. Kaplan-Meier analysis was performed to validate the prognostic value of hub genes. Mutational characteristics of UCEC patients according to PD1 levels were depicted and analyzed. We found that the transcriptional expression of the PD1 gene in UCEC tumor tissues markedly increased in cohorts from the GEPIA and TCGA databases. PD1 expression was negatively correlated with gene signatures associated with the T-cell receptor signaling pathway and primary immunodeficiency. GESA confirmed that PD1 expression was negatively correlated with gene signatures associated with the T-cell receptor signaling pathway. T-cell receptor complex-related genes, ZAP70, TRAC, CD3D, CD3E, CD8A, TRBC2, TRBV28 and CD247, showed significant positive associations with PD1 expression. The results of the Kaplan-Meier OS analysis indicated that PD1, TIGIT, FASLG, ICOS and TNFRSF9 are the protective factor for patients with UCEC. The top 5 genes of mutations in the low expression group, included PTEN (56%), PIK3CA (43%), TP53 (41%), TTN (39%), and ARID1A (37%). The genes with a higher proportion of mutations in the PD1-high group are PTEN (67%), TTN (62%), PIK3CA (53%), ARID1A (52%), and MUC16 (12%). The prognosis of UCEC patients with PD1 overexpression phenotype is worse than that of the PD1 low group, which is due to the involvement of the PD1 gene in the T-cell receptor signaling pathway. This study provides a further theoretical basis and reference for targeted therapy against PD1.